2016
DOI: 10.1681/asn.2015050555
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirements for Vacuolar Protein Sorting 34 Downstream Effector Phosphatidylinositol 3-Phosphate 5-Kinase in Podocytes Versus Proximal Tubular Cells

Abstract: The mechanisms by which the glomerular filtration barrier prevents the loss of large macromolecules and simultaneously, maintains the filter remain poorly understood. Recent studies proposed that podocytes have an active role in both the endocytosis of filtered macromolecules and the maintenance of the filtration barrier. Deletion of a key endosomal trafficking regulator, the class 3 phosphatidylinositol (PtdIns) 3-kinase vacuolar protein sorting 34 (Vps34), in podocytes results in aberrant endosomal membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…For example, terminally differentiated 3T3L1 adipocytes in culture, as opposed to the rapidly dividing precursor 3T3L1 fibroblastic cells, do not form cytoplasmic vacuoles under pharmacological inhibition or expression of the dominantinterfering kinase-deficient mutant of PIKfyve (27,50). Likewise, fat cells, muscle cells, or glomeruli podocytes in the context of the respective adipose-specific, muscle-specific or podocytes-specific mouse model with Pikfyve inactivation through Cre recombinase expression driven by the corresponding promoters, do not exhibit cytoplasmic vacuoles in situ (22,23,28,64). Whereas in these mouse models incomplete Pikfyve inactivation might be an admissible cause for lack of vacuoles, it is remarkable that mitotic podocytes that outgrow in a culture from the very same nonvacuolating terminally differentiated glomerular podocytes exhibit the vacuolation phenomenon (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, terminally differentiated 3T3L1 adipocytes in culture, as opposed to the rapidly dividing precursor 3T3L1 fibroblastic cells, do not form cytoplasmic vacuoles under pharmacological inhibition or expression of the dominantinterfering kinase-deficient mutant of PIKfyve (27,50). Likewise, fat cells, muscle cells, or glomeruli podocytes in the context of the respective adipose-specific, muscle-specific or podocytes-specific mouse model with Pikfyve inactivation through Cre recombinase expression driven by the corresponding promoters, do not exhibit cytoplasmic vacuoles in situ (22,23,28,64). Whereas in these mouse models incomplete Pikfyve inactivation might be an admissible cause for lack of vacuoles, it is remarkable that mitotic podocytes that outgrow in a culture from the very same nonvacuolating terminally differentiated glomerular podocytes exhibit the vacuolation phenomenon (64).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, fat cells, muscle cells, or glomeruli podocytes in the context of the respective adipose-specific, muscle-specific or podocytes-specific mouse model with Pikfyve inactivation through Cre recombinase expression driven by the corresponding promoters, do not exhibit cytoplasmic vacuoles in situ (22,23,28,64). Whereas in these mouse models incomplete Pikfyve inactivation might be an admissible cause for lack of vacuoles, it is remarkable that mitotic podocytes that outgrow in a culture from the very same nonvacuolating terminally differentiated glomerular podocytes exhibit the vacuolation phenomenon (64). Concordantly, Pikfyve inactivation in cells that are under robust and constant turnover, such as proximal tubular and intestinal epithelial cells, readily trigger cytoplasmic vacuoles in situ in the respective tissue-specific Pikfyve KO mouse model (61,64).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence intensity of HABP staining was quantified using integrated density analysis as previously described [37,38]. For all the RPE cell culture confocal microscopy images, fluorescence was quantitated using a standard measure of integrated density, which is the product of area and mean gray value.…”
Section: Quantitation Of Immunofluorescence By Integrated Density Anamentioning
confidence: 99%
“…A hypomorphic PIKfyve mouse model is viable, but it dies early due to defects in multiple organs and tissues, including neural tissues, heart, lung, kidney, thymus, and the hematopoietic system (20). Subsequently, conditional PIKfyve knockout mice were developed using the Cre-Lox system and demonstrated the essential roles of PIKfyve in specific tissues (19,(21)(22)(23)(24)(25)(26). In particular, we previously showed that mice with platelet-specific deletion of PIKfyve have impaired lysosomal homeostasis and develop aberrant inflammatory and prothrombotic responses (22).…”
mentioning
confidence: 99%